Between Laborer and Slave: The Fate of Contract Coolies in Colonial East Sumatra Plantation - Anatona Anatona (Andalas International Journal of Socio-Humanities, 2024)
Broadly speaking, both laborers (or coolies) and slaves served as manual workers engaged in arduous physical tasks. However, distinctions arise not only from the historical origins of these terms but also from their definitions and conceptual frameworks. Key differences between laborers and slaves pertain to social status, identity, rights and obligations, interpersonal relationships with employers, and the nature of treatment received. Despite these fundamental differences, the practical reality often diverged. There are instances where laborers or coolies were treated in ways akin to slaves. This article aims to discuss and examine the extent to which such treatment was experienced by plantation workers in the Dutch colonial era, known as contract coolies, in the East Sumatra region. The issue is reconstructed and analyzed through a historical lens, spanning the late 19th to early 20th centuries, marked by the establishment of plantation centers in the Dutch East Indies by foreign entrepreneurs, including those in East Sumatra. Examination of available historical sources reveals that a portion of these contract coolies endured harsh and inhumane treatment, mirroring the experiences of slaves in various other contexts.